Systematic Literature Review of Social Support Conditions for Students with Special Needs in Inclusive Schools - Paryanto Paryanto; Wahyu Nanda Eka Saputra; Agus Supriyanto (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Inclusive education requires a supportive learning environment that enables students with special needs to participate, develop, and achieve optimal educational outcomes. Social support from teachers, peers, families, school counselors, and policymakers plays a critical role in strengthening students’ academic adjustment, self-efficacy, social interaction, and psychological well-being. This study aimed to identify, analyze, and synthesize previous research on social support for students with special needs in inclusive schools. A systematic literature review was conducted using the PRISMA framework to guide the identification, screening, eligibility assessment, and inclusion of relevant studies. Articles were retrieved from Google Scholar and selected based on relevance to the topic, publication period, and suitability for the research objectives. The final review included 17 relevant studies published between 2020 and 2025. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing through critical extraction and comparison of research findings. The results indicate that social support is a key predictor of successful inclusive education. Comprehensive support from teachers, peers, and families contributes to improved learning outcomes, self-efficacy, social skills, learning motivation, academic achievement, and psychological well-being among students with special needs. Inclusive school environments also help reduce social anxiety and foster empathy, acceptance, and positive interaction between students with special needs and regular students. These findings highlight the importance of systematic, structured, and collaborative efforts involving subject teachers, guidance and counseling teachers, school policymakers, peers, and families. This study implies that inclusive schools need to strengthen cross-sector collaboration and develop sustainable support systems to create friendly, responsive, and equitable learning environments for students with diverse needs.